Assessing Patients' Knowledge on Chronic Lymphocytic Leukemia: Validation of the ERIC CLL Knowledge Questionnaire in Greece. Issue 3 (23rd March 2021) - Karamanidou, Christina; Xochelli, Aliki; Papaioannou, Maria; Moysiadis, Theodoros; Scarfo, Lydia; Mattsson, Mattias; Stavroyianni, Niki; Rosenquist, Richard; Ghia, Paolo; Stamatopoulos, Kostas
Abstract : Supplemental Digital Content is available in the text.